Pathomechanisms in Lysosomal Storage Disorders - Walkley, Steven U. (Biochim Biophys Acta, 2008)
Lysosomal diseases are inherited metabolic disorders caused by defects in a wide spectrum of lysosomal and a few non-lysosomal proteins. In most cases a single type of primary storage material is identified, which has been used to name and classify the disorders: hence the terms sphingolipidoses, gangliosidoses, mucopolysaccharidoses, glycoproteinoses, and so forth. In addition to this primary storage, however, a host of secondary storage products can also be identified, more often than not having no direct link to the primary protein defect. Lipids - glycosphingolipids and phospholipids, as well as cholesterol - are the most ubiquitous and best studied of these secondary storage materials. While in the past typically considered nonspecific and nonconsequential features of these diseases, newer studies suggest direct links between secondary storage and disease pathogenesis and support the view that understanding all aspects of this sequestration process will provide important insights into the cell biology and treatment of lysosomal disease.